Status of the Children's Socio-Emotional Well-being Before and During the Pandemic: A Scoping Review - Bagay, Milojean O.; Empinado, Joanne Chris T.; Lambo, Kharylle Xyrra A.; Caingcoy, Manuel E. (International Journal of Business, Law, and Education, 2024)
Positive mental health thrives on strong social and emotional connections. Cultivating a child's ability to forge close, secure, and meaningful relationships is the cornerstone of well-being. Yet, pandemic-induced isolation has created barriers to face-to-face interaction with friends, posing a significant challenge to this critical developmental task. This scoping review delves into previous research concerning children's socio-emotional well-being before and during the pandemic. We screened studies, focusing solely on those directly addressing the core issues impacting children's emotional landscape. Our findings reveal disturbing trends: the pandemic has amplified anxieties, particularly among vulnerable children. The evidence speaks for itself – this global health crisis has inflicted a negative impact on children's socio-emotional health. In response, researchers have proposed a range of policy recommendations to equip teachers and parents with the tools to recognize and mitigate the pandemic's consequences on children. Among these, ongoing debriefing sessions for teachers can foster understanding and gradually alleviate anxieties that ripple through classrooms. Simultaneously, parents – as children's primary caregivers – must remain informed and offer unwavering support, actively monitoring and addressing anxieties within their homes.